Effectiveness and Safety of Adding Bevacizumab to Platinum-Based Chemotherapy as First-Line Treatment for Advanced Non-Small-Cell Lung Cancer: A Meta-Analysis - Liu, Yi; Li, Hui-Min; Wang, Ran (Frontiers in Medicine, 2021)
Background and Objective: Previous studies have evaluated the efficacy (OS, overall survival; PFS, progression-free survival; ORR, objective response rate) and adverse events of bevacizumab combined with platinum-based chemotherapy in first-line treatment of advanced non-small-cell lung cancer (NSCLC) compared with chemotherapy alone. However, the results were inconsistent. Methods: We conducted a comprehensive search of PubMed, EMBASE, and Cochrane Library for potentially eligible articles. The outcomes were evaluated in terms of risk ratio (RR) or hazard ratio (HR) and the associated 95% confidence intervals (CIs). Meta-analysis was performed using the Stata 12.0 software, and subgroup analyses were performed based on the treatment and bevacizumab dose. Results: Six randomized controlled trials with 2,465 patients were included in this meta-analysis. The results demonstrated that bevacizumab significantly increased OS (HR = 0.87, 95% CI 0.79–0.96), extended PFS (HR = 0.65, 95% CI 0.54–0.77), and increased ORR (ES = 0.40, 95% CI 0.31–0.48) when added to first-line platinum-based chemotherapy in patients with advanced NSCLC. Subgroup analyses showed that only the higher dose (15 mg/kg) of bevacizumab plus carboplatin–paclitaxel significantly extended the OS and PFS, but both 7.5 mg/kg and 15 mg/kg of bevacizumab improved ORR. However, both 7.5 mg/kg and 15 mg/kg of bevacizumab could only increase PFS and ORR, but not extend OS, when added to cisplatin–gemcitabine. Bevacizumab significantly increased the risk of grade ≥3 events of febrile neutropenia, haemorrhagic events, hypertension, leukopenia, neutropenia, and proteinuria. Conclusion: Bevacizumab significantly increases OS, PFS, and ORR when added to first-line platinum-based chemotherapy in patients with advanced NSCLC, with no new safety signals found. Moreover, bevacizumab (15 mg/kg) plus carboplatin–paclitaxel is a better alternative in increasing OS to carboplatin–paclitaxel and bevacizumab (7.5 mg/kg and 15 mg/kg) plus cisplatin–gemcitabine.